2022
DOI: 10.1186/s12917-022-03252-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of transposon systems in the transgenesis of bovine somatic and germ cells

Abstract: Background Several DNA transposons including PiggyBac (PB), Sleeping Beauty (SB), and Tol2 have been applied as effective means for of transgenesis in many species. Cattle are not typically experimental animals, and relatively little verification has been presented on this species. Thus, the goal here was to determine the applicability of three transposon systems in somatic and embryo cells in cattle, while also investigating which of the three systems is appropriate for each cell type. Green f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although a study reported that Tg rats can be produced more efficiently (33%–100%, mean of nearly 80%) using mPBase mRNA pronuclear microinjection 50 , it may be possible to consistently produce Tg animals even more efficiently if mPBase mRNA is introduced at an earlier timing after in vitro fertilization. Transgenic technology is also important for livestock, such as cattle, pig, and sheep, but there are very limited reports on application of the piggyBac transposon system to their zygotes 51,52 . Somatic cell nuclear transfer is one of the most common methods to create Tg livestock 53,54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a study reported that Tg rats can be produced more efficiently (33%–100%, mean of nearly 80%) using mPBase mRNA pronuclear microinjection 50 , it may be possible to consistently produce Tg animals even more efficiently if mPBase mRNA is introduced at an earlier timing after in vitro fertilization. Transgenic technology is also important for livestock, such as cattle, pig, and sheep, but there are very limited reports on application of the piggyBac transposon system to their zygotes 51,52 . Somatic cell nuclear transfer is one of the most common methods to create Tg livestock 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted December 10, 2023. ; https://doi.org/10.1101/2023.12.10.570953 doi: bioRxiv preprint timing after in vitro fertilization. Transgenic technology is also important for livestock, such as cattle, pig, and sheep, but there are very limited reports on application of the piggyBac transposon system to their zygotes 51,52 . Somatic cell nuclear transfer is one of the most common methods to create Tg livestock 53,54 .…”
Section: Discussionmentioning
confidence: 99%